The politics of the governed : reflections on popular politics in most of the world - Chatterjee, Partha, 1947- (University seminars/Leonard Hastings Schoff memorial lectures., 2004)
Often dismissed as the rumblings of "the street," popular politics is where political modernity is being formed today, according to Partha Chatterjee. The rise of mass politics all over the world in the twentieth century led to the development of new techniques of governing population groups. On the one hand, the idea of popular sovereignty has gained wide acceptance. On the other hand, the proliferation of security and welfare technologies has created modern governmental bodies that administer populations, but do not provide citizens with an arena for democratic deliberation. Under these conditions, democracy is no longer government of, by, and for the people. Rather, it has become a world of power whose startling dimensions and unwritten rules of engagement Chatterjee provocatively and disturbingly lays bare. This book argues that the rise of ethnic or identity politics -particularly in the postcolonial world -is a consequence of the new techniques of governmental administration. Using contemporary examples from India, the book examines the different forms taken by the politics of the governed. Many of these operate outside of the traditionally defined arena of civil society and the formal legal institutions of the state. This book considers the global conditions within which such local forms of popular politics have appeared and shows us how both community and global society have been transformed. Chatterjees analysis permits a new understanding of the dynamics of world politics both before and after the events of September 11, 2001